2010
DOI: 10.1111/j.1471-4159.2010.06671.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging and c‐Fos mapping in rats following a glucoprivic dose of 2‐deoxy‐d‐glucose

Abstract: J. Neurochem. (2010) 113, 1123–1132. Abstract The glucose analogue, 2‐deoxy‐d‐glucose (2‐DG) is an inhibitor of glycolysis and, when administered systemically or centrally, induces glucoprivation leading to counter‐regulatory responses, including increased feeding behaviour. Investigations into how the brain responds to glucoprivation could have important therapeutic potential, as disruptions or defects in the defence of the brain’s ‘glucostatic’ circuitry may be partly responsible for pathological conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
(71 reference statements)
3
20
0
Order By: Relevance
“…Thus, for this region, the results did not support our hypothesis that decreased FDG uptake in a specific region will directly relate to decreased IEG expression (Levine et al, 2007(Levine et al, , 2008. As mentioned above, this may reflect the inexact correspondence between IEG expression and functional neuroimaging, as these two techniques measure both similar and different types of neuronal activity changes (Guzowski et al, 2006;Stark et al, 2006;Marrone et al, 2008;Dodd et al, 2010). Still given that many studies suggest reduced mPFC neuronal activity in IR rats, the possibility that the nonstatistically significant trend (p = 0.09) we found for decreased mPFC uptake is a result of the low sample size of the current study should be considered as well, as for this ROI the study was underpowered.…”
Section: Changes In Fdg Uptake In the Mpfcmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, for this region, the results did not support our hypothesis that decreased FDG uptake in a specific region will directly relate to decreased IEG expression (Levine et al, 2007(Levine et al, , 2008. As mentioned above, this may reflect the inexact correspondence between IEG expression and functional neuroimaging, as these two techniques measure both similar and different types of neuronal activity changes (Guzowski et al, 2006;Stark et al, 2006;Marrone et al, 2008;Dodd et al, 2010). Still given that many studies suggest reduced mPFC neuronal activity in IR rats, the possibility that the nonstatistically significant trend (p = 0.09) we found for decreased mPFC uptake is a result of the low sample size of the current study should be considered as well, as for this ROI the study was underpowered.…”
Section: Changes In Fdg Uptake In the Mpfcmentioning
confidence: 64%
“…Having previously identified that IR rats had decreased immediate early gene (IEG) expression in the mPFC and hippocampus (Levine et al, 2007(Levine et al, , 2008Vitalo et al, 2009), we hypothesized that these regions would show decreased FDG uptake. This hypothesis was based on the fact that both PET FDG and IEG expression reflect changes in neural activity and several studies have now shown that brain imaging of neuronal activity correlates with IEG expression (Lu et al, 2004;Stark et al, 2006;Dodd et al, 2010), although IEG expression does reflect some forms of neuronal activity change that are not detected by PET imaging (Guzowski et al, 2006;Stark et al, 2006;Marrone et al, 2008;Dodd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have been using these templates for localization of BOLD fMRI (Ramu et al, 2006; Endo et al, 2007; Reyt et al, 2010; Sumiyoshi et al, 2011), position emission tomography (PET; Fujita et al, 2005; Casteels et al, 2006; Frumberg et al, 2007; Hjornevik et al, 2008; Sung et al, 2009), pharmacological MRI (phMRI; Gozzi et al, 2007, 2008; Schwarz et al, 2007; Dodd et al, 2010), or manganese-enhanced MRI (MEMRI; Eschenko et al, 2010). In contrast, our registration method sought for the MDT of our sample, avoiding a bias in registration methods toward those heads most similar to the template (Guimond, 2000; Kochunov et al, 2001a,b).…”
Section: Discussionmentioning
confidence: 99%
“…On the cellular level, others have shown high glucose can increase c-Fos expression in rat PVN neurons [10, 17] and high glucose diets can produce increases in intracellular Ca 2+ in PVN neurons in mice [22]. However, differences between brain activity measured by fMRI and markers of activity (c-Fos) in single neurons have been documented elsewhere [16, 55, 63] and show that these methods can yield conflicting results. Also, chronic and acute high glucose should not be expected to produce similar effects on neuronal activity.…”
Section: Discussionmentioning
confidence: 99%